Pendidikan karakter berbasis e-comic sebagai upaya pencegahan pernikahan dini di MTs Diponegoro Jatikerto - Yuliastuty, Devi Sintya; Qumairoh, Iftitah Dian; Maulidina, Fachrin (Universitas Negeri Malang, 2023)
Data from the Class 1 A Religious Court in Malang Regency noted that throughout 2022 there were 1,455 cases of child marriage under the age of 18. This has become the focus of many parties, especially the Office of Women's Empowerment and Child Protection of Malang Regency. Based on these problems, the author provides efforts to prevent early marriage by creating a program namely